Fiscal Policies and Asset Prices - Croce, M. Max; Kung, Howard; Nguyen, Thien T.; Schmid, Lukas (Review of Financial Studies, 2012)
The surge in public debt triggered by the financial crisis has raised uncertainty about future tax pressure and economic activity. We examine the asset pricing effects of fiscal policies in a production-based general equilibrium model in which taxation affects corporate decisions by: (1) distorting profits and investment; (2) reducing the cost of debt through a tax shield; and (3) depressing productivity growth. In settings with recursive preferences, these three tax-based channels generate sizable risk premia, making tax uncertainty a first-order concern. We document further that corporate tax smoothing can substantially alter the effects of public expenditure shocks. The Author 2012. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.